Transcriptional regulation of INK4/ARF locus by cis and trans mechanisms - Farooq, Umer; Notani, Dimple (Frontiers in Cell and Developmental Biology, 2022)
9p21 locus is one of the most reproducible regions in genome-wide association studies (GWAS). The region harbors CDKN2A/B genes that code for p16INK4a, p15INK4b, and p14ARF proteins, and it also harbors a long gene desert adjacent to these genes. The polymorphisms that are associated with several diseases and cancers are present in these genes and the gene desert region. These proteins are critical cell cycle regulators whose transcriptional dysregulation is strongly linked with cellular regeneration, stemness, aging, and cancers. Given the importance of this locus, intense scientific efforts on understanding the regulation of these genes via promoter-driven mechanisms and recently, via the distal regulatory mechanism have provided major insights. In this review, we describe these mechanisms and propose the ways by which this locus can be targeted in pathologies and aging.